Use of Laryngeal Computed Tomography for Noninvasive Assessment of Laryngeal Function in Horses with Recurrent Laryngeal Neuropathy. (September 2014) - Tulloch, L.K.; Piercy, R.J.; Troester, S.; Carruthers, R.; Tast, V.; Grimes, L.; Perkins, J.D.
Abstract : Reasons for performing study: Recurrent laryngeal neuropathy (RLN) is a common equine distal axonopathy associated with neurogenic atrophy of intrinsic laryngeal muscles (particularly the left) causing laryngeal paresis and poor performance. An objective, reliable method of assessing changes in structure that correlates with laryngeal muscle function in vivo is necessary to determine response to novel treatments, including functional electrical stimulation. This study aimed to determine whether laryngeal muscle and nerve morphology (determined by CT and histopathology) correlated with laryngeal function. Study design: Prospective cohort study. Methods: Resting ( grades 1–4 ) and exercising ( grades A–C ) laryngeal function was graded in adult Thoroughbred horses. Standing CT of the larynx was performed to compare volume, cross‐sectional area (XSA) and tissue density between left and right cricoarytenoideus dorsalis (CAD) muscles in 22 horses. CAD muscles and recurrent laryngeal nerves were collected in a subgroup of 10 horses and analysed for fibrosis, fat infiltration and nerve fibre density (axons/μm 2 ). Results: Horses with grade C RLN on exercising endoscopy had significantly (P<0.005) smaller left CAD muscles and reduced nerve fibre density than horses with grades A or B . Horses with grade 4 RLN on resting endoscopy had significantly (P<0.005) smaller left CAD muscles than horses with grades 1 or 2 . Left CAD muscles had significantly more collagen than the right in horses with grade C RLN. CT measurements of the CAD muscles were significantly associated with % collagen/fat and nerve fibre density (P<0.05). Conclusions: Laryngeal CT results correlate with laryngeal function at rest and exercise in the horse and provide a noninvasive method of monitoring changes in CAD morphology in response to novel treatments. CAD CT appearance is dependent on % collagen and fat in the muscle and is associated with nerve fibre density. Ethical animal research: Horses destined for euthanasia were recruited for this study with approval of the Institutional Ethical Committee and under UK Home Office Licence.Sources of funding: Med‐El Elektro‐medizinische Geräte GmbH, Innsbruck, Austria.Competing interests: None.